2020
DOI: 10.1128/jvi.01206-20
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Enhances Antiviral CD4+Tissue-Resident Memory T Cell Responses following Mucosal Herpes Simplex Virus 2 Vaccination through an IL-17-Mediated Pathway

Abstract: Estradiol (E2) is a sex hormone which has shown to be protective against sexually transmitted infections such as herpes simplex virus 2 (HSV-2). However, few studies have examined the underlying mechanisms by which this occurs. Here, we investigated the effect of E2 on the establishment of memory T cells post-intranasal immunization with HSV-2. CD4+ T cell responses first appeared in the upper respiratory tract (URT) within 3 days post-immunization, before being detected in the female reproductive tract (FRT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Our work over the past few years has provided significant insight regarding how IL-17 modulates critical anti-viral T cell responses in the FRT. While it is well established that anti-viral protection against HSV-2 in the mouse model of infection is largely mediated by Th1 responses ( 115 117 ), our findings are the first to show that Th17 responses are also important in the anti-viral immune response to HSV-2 infection ( 118 120 ). We directly examined the role of IL-17 in anti-viral protection against HSV-2 and found that compared to WT controls, IL-17A-/- mice immunized intravaginally or intranasally were more susceptible to HSV-2 challenge ( 119 ).…”
Section: Viral Infectionsmentioning
confidence: 41%
See 1 more Smart Citation
“…Our work over the past few years has provided significant insight regarding how IL-17 modulates critical anti-viral T cell responses in the FRT. While it is well established that anti-viral protection against HSV-2 in the mouse model of infection is largely mediated by Th1 responses ( 115 117 ), our findings are the first to show that Th17 responses are also important in the anti-viral immune response to HSV-2 infection ( 118 120 ). We directly examined the role of IL-17 in anti-viral protection against HSV-2 and found that compared to WT controls, IL-17A-/- mice immunized intravaginally or intranasally were more susceptible to HSV-2 challenge ( 119 ).…”
Section: Viral Infectionsmentioning
confidence: 41%
“…For the past decade we have investigated the influence of E2 on immune responses in the FRT and found that E2 increases protection against HSV-2 infection, although the underlying immunological mechanisms remained unclear. Recently, we showed that better protection in E2-treated mice coincided with earlier recruitment and higher proportions of Th1 and Th17 cells in the FRT following either HSV-2 immunization (intravaginally or intranasally) ( 120 ) and/or challenge ( 118 ). This included greater establishment of tissue-resident memory CD4+ T cells in the FRT, which play a critical role against re-exposure to pathogens ( 120 ).…”
Section: Viral Infectionsmentioning
confidence: 99%
“…For example, oestradiol has been described to enhance the neutralising antibody titre in mouse models of infection with genital herpesvirus type II (HSV-2) infection ( [30,31]) and H1N1 [17]. Furthermore, in another vaccination model of HSV-2, oestradiol has been shown to increase dendritic cell activity by producing inflammatory cytokines such as IL-1beta [32] and more recently, this hormone has also been shown to increase the number of CD4+ memory T cells in tissue through a IL-17 mediated pathway [33].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative option to boost the formation of T RM cells involves hormonal treatments. Hereby, the co-administration of estradiol after initial intranasal immunization with HSV-2 led to increased Th1 and Th17 T RM cell frequencies with protective capabilities upon genital HSV-2 re-challenge [ 28 ].…”
Section: Tissue-resident Immunity In the Vaginamentioning
confidence: 99%